IL-1 & IL-6 in Bone: Local Translators in Cell-to-Cell Communications - Sri Angky Soekanto (Faculty of Dentistry, Universitas Indonesia, 2015)
Interleukin-1 (IL-1) and interleukin-6 (IL-6) which are produced in bone marrow cells and bone cells play an important roles as local mediators between cells in the bone microenvironment. These interleukin of osteotropic cytokines have important regulatory roles in many organ processes, such as embryogenesis, angiogenesis, tumorigenesis, wound healing, and immune responses. The major targets of these cytokines in the bone is progenitor cells, and in particular, hematopoietic precursors of osteoclasts, are strongly influenced by these cytokines. Proliferation and differentiation of osteoblasts are modulated by IL-1 and IL-6 through autocrine and/or paracrine mechanisms. IL-1 and IL-6 both have the action on bone formation and resorption in normal and pathologic bone turnover. However, it seems almost impossible to clearly elucidate their roles. Further investigation are needed to give more information on the role of osteotropic cytokines in bone cell function that will advance bone research.